2006
DOI: 10.1158/0008-5472.can-06-0410
|View full text |Cite
|
Sign up to set email alerts
|

Reassessing Epithelial to Mesenchymal Transition as a Prerequisite for Carcinoma Invasion and Metastasis

Abstract: For most carcinomas, progression toward malignancy is accompanied by loss of epithelial differentiation and a shift towards a mesenchymal phenotype. This process, referred to as epithelial to mesenchymal transition (EMT), exacerbates motility and invasiveness of many cell types and is often considered a prerequisite for tumor infiltration and metastasis. However, there are numerous examples of advanced carcinomas that adopt some mesenchymal features, yet retain characteristics of well-differentiated epithelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

28
821
1
11

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 939 publications
(866 citation statements)
references
References 82 publications
28
821
1
11
Order By: Relevance
“…3,4 Our work demonstrated that the loss of E-cadherin itself, without a mesenchymal phenotype, may not be associated with invasive behavior, whereas tumors with a mesenchymal phenotype, regardless of E-cadherin expression, showed aggressive behavior in esophageal squamous cell carcinoma. Recently, Uchikado et al 21 reported that the patients with esophageal squamous cell carcinoma who were positive for Slug expression had deeper tumor invasion and worse prognosis in the E-cadherin preserved group.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…3,4 Our work demonstrated that the loss of E-cadherin itself, without a mesenchymal phenotype, may not be associated with invasive behavior, whereas tumors with a mesenchymal phenotype, regardless of E-cadherin expression, showed aggressive behavior in esophageal squamous cell carcinoma. Recently, Uchikado et al 21 reported that the patients with esophageal squamous cell carcinoma who were positive for Slug expression had deeper tumor invasion and worse prognosis in the E-cadherin preserved group.…”
Section: Discussionmentioning
confidence: 75%
“…In addition, because of the dynamic and reversible nature of epithelial-mesenchymal transition, numerous advanced carcinomas that adopt some mesenchymal features retain the characteristics of well-differentiated epithelial cells. 3,4 In vivo, epithelial-mesenchymal transition phenotypes include the extremes, ranging from an epithelial phenotype to a complete mesenchymal phenotype with a variety of intermediate sub-phenotype combinations between these extremes. Examples of intermediate sub-phenotypes include the 'hybrid type' that is a mixed epithelial and mesenchymal phenotype and the 'null type' that can be defined as the loss of the epithelial phenotype without acquisition of mesenchymal phenotype.…”
mentioning
confidence: 99%
“…One of the most important arguments against the existence of epithelial-mesenchymal transition in human solid tumors is that it has not been identified in most cases. 40,41 This could be due to the clonal heterogeneity of epithelial-mesenchymal transition in primary tumors, that is, cells that have undergone …”
Section: Discussionmentioning
confidence: 99%
“…During EMT, epithelial cells lose the characteristics of epithelial cells (cell junctions, apical-basal polarity and contact inhibition) and gain a mesenchymal phenotype including enhanced invasiveness, increased cell-to-extracellular matrix contact and resistance to apoptosis [23]. In addition, epithelial cells reduce the expression of epithelial markers (epithelial keratins, E-cadherin and ÎČ-catenin) and upregulate mesenchymal markers (vimentin and fibronectin) [24,25].…”
Section: Resultsmentioning
confidence: 99%